Smallholder Oil Palm Production in the Peruvian Amazon: Rethinking the Promise of Associations and Partnerships for Economically Sustainable Livelihoods - Bennett, Aoife; Ravikumar, Ashwin; McDermott, Constance; Malhi, Yadvinder (Frontiers in Forests and Global Change, 2019)
Smallholders play a major role in the expansion of oil palm as a global commodity crop. Yet outside of Southeast Asia, there is limited research on how it impacts smallholder livelihoods. This paper examines how different smallholder modes of production have emerged in the largest oil palm producing region of the Peruvian Amazon, Ucayali, and presents a typology of these arrangements. The socio-economic outcomes of these modes are analyzed using a survey of 200 smallholders and 14 months of participant observation. Results show that there is considerable variation in how smallholders produce oil palm, and in the outcomes associated with different production strategies. Independent production, corporate partnerships, and government assistance programs were viewed positively by smallholders. However, smallholders’ knowledge about the workings of the market, the role of associations, and their own financial circumstances was poor. Different modes of production yield different outcomes in terms of debt burdens, dependency on powerful actors for information, and crop and livelihood diversity. These outcomes had implications for the economic sustainability of oil palm for smallholder livelihoods. Importantly, corporate partnerships have generated comparatively massive debt burdens for smallholders. On the other hand, under other production scenarios smallholders may hold significant power over decisions, and can benefit economically from oil palm, which has important implications for ethical oil-palm debates and decision making.